Using shallow neural networks for strategic management in hotel and restaurant industry - Liavynets, Heorhii; Zahorui, Oksana (My University, 2025)
Стаття досліджує використання дрібних штучних нейронних мереж у стратегічному управлінні готелями та ресторанами. Він демонструє покращення процесу прийняття рішень завдяки сегментації клієнтів, оптимізації цін і оцінці ризиків. Дослідження підтверджує, що ці моделі підвищують операційну ефективність і стійкість, особливо в умовах економічної нестабільності, підвищуючи прибутковість і довгострокову конкурентоспроможність у сфері гостинності. The paper explores the use of shallow artificial neural networks in hotel and restaurant strategic management. It demonstrates improved decision-making through customer segmentation, pricing optimization, and risk assessment. The study confirms these models enhance operational efficiency and resilience, especially under economic instability, boosting profitability and long-term competitiveness in hospitality.
Keywords: кафедра готельно-ресторанної справи; hospitality business; Neural Networks